Biochemical and molecular differentiation of Anacroneuria species (Plecoptera, Insecta) in Andean National Park, Venezuela. Issue 7 (3rd October 2019) - Gamboa, Maribet; Arrivillaga-HenrÍQuez, Jazzmin
Abstract : Inferring species boundaries or speciation events is not straightforward as these processes are often fuzzy and difficult to identify. This may be simplified by the use of integrative approaches that combine molecular and biochemical techniques. Here, we examined four stoneflies species differentiation using a combination of genetic signals involving mitochondrial genetic markers (cytochrome oxidase, cox1, and 12S ) and biochemical signals involving cuticular hydrocarbons. A combination of both the techniques revealed strong interactions among Anacroneuria species and potential recent speciation events refuting species hypothesis from three out of four species despite consistent morphological differences, which enhance our understanding of species divergence in Anacroneuria species. Our results may serve as a basis for further studies assessing species boundaries and evolutionary relationships among other insect species for biodiversity implications on river management.